Associations of environmental variables with different types of stroke - Vaičiulis, Vidmantas; Venclovienė, Jonė; Radišauskas, Ričardas; Krančiukaitė-Butylkinienė, Daina; Tamošiūnas, Abdonas; Rastenytė, Daiva (European Journal of Public Health, 2019)
Article no. ckz186.240 Background Air temperature (T) and atmospheric pressure (AP) are among the most closely studied weather variables; increases, decreases, and fluctuations in both have been significantly linked to numerous stroke subtypes. We decided to detect the association between daily numbers of ischaemic stroke (IS) and haemorrhagic stroke (HS) and daily North Atlantic Oscillation (NAO) and Arctic Oscillation (AO) indices and monthly indices of Quasi-Biennal Oscillation (QBO). Methods The study was conducted in Kaunas city from 2000 to 2010. Kaunas stroke register presented daily numbers of IS, subarachnoid haemorrhages (SAH), and intracerebral haemorrhages (ICH). We evaluated the association between these types of stroke and NAO, AO, and QBO indices (NAOI, AOI, and QBOI) by applying Poisson regression, adjusting for month and other weather variables. Results During the study period, we analysed 3,992 cases (2,205 men and 1,787 women) with stroke. IS composed 3,199 (80.1%), ICH 533 (13.4%), and SAH - 260 (6.5%). A change in mean daily atmospheric pressure (AP) of > 3.9 hPa and QBOI <-27 were associated with the risk of SAH (RRs with 95% CI were, respectively, 1.54 (1.18-2.03), and 1.68 (1.06-2.66)). The risk of HS was associated with daily increases in AP and QBOI <8.37 (p < 0.05). The risk of IS was negatively associated with AOI (RR = 0.97 (0.94-0.99). During November-March, NAOI >0 was associated with HS (RR = 1.29 (1.03-1.62)), and a negative association between NAOI and IS (RR = 0.91 (0.84-0.98)) was found. Conclusions The results of our study provided new evidence that the NAO, AO, and QBO pattern may affect the risk of stroke. The impact of these teleconnection indices is not identical for different types of stroke. Key messages This abstract is part of publication, which will be published later on.[.] Aplinkotyros katedra Lietuvos sveikatos mokslų universitetas. Medicinos akademija Vytauto Didžiojo universitetas